NOXA exacerbates endoplasmic-reticulum-stress-induced intervertebral disc degeneration by activating apoptosis and ECM degradation - Zhiming Liu; Hui Lu; Xianjuan Zhang; Shuai Tang; Antao Lin; Shuo Han; Xuexiao Ma (Cell Death Discovery)
Abstract Intervertebral disc degeneration (IVDD) is a prevalent condition leading to low back pain. Endoplasmic reticulum stress (ERS) is strongly linked to IVDD progression, although the underlying mechanisms remain unclear. In this study, we investigated the effects of NOXA on ERS-induced IVDD. Primary nucleus pulposus cells (NPCs) were stimulated with Thapsigargin to mimic the ERS microenvironment in IVDD. Western blot analysis, PCR, immunofluorescence, and immunohistochemistry assay were performed to measure the expression levels of PERK, NOXA, and cell apoptosis- and extracellular-matrix-degradation-relevant proteins. JC-1 fluorescent probes, terminal deoxynucleotidyl transferase dUTP nick end labeling staining, and flow cytometry were used to measure mitochondrial function and apoptosis in NPCs under ERS conditions. Magnetic resonance imaging, Safranin O staining, alcian blue staining, and immunohistochemistry were performed to estimate the effects of NOXA knockdown on acupuncture-mediated IVDD in rats at both imaging and histological levels. The results showed that ERS induced and activated the PERK pathway during IVDD development. Mechanically, ERS induced NPC apoptosis and ECM degradation by upregulating PERK expression and activating NOXA expression. The genetic overexpression of NOXA inhibited cell proliferation and increased apoptosis, whereas its knockdown decreased MCL-1 expression and alleviated IVDD degeneration in human NPCs and rat models. NOXA plays a crucial role in the PERK/NOXA/MCL-1 axis, mediating the link between ERS and IVDD. Targeting NOXA expression may be an effective method for treating IVDD, laying the foundation for future research on molecular mechanisms and the development of new therapies.